The mobility of memory migrations and diasporas across European borders - Passerini, Luisa 1941-; Proglio, Gabriele (Berghahn Books, 2021)
"Migration is most concretely defined by the movement of human bodies, but it leaves indelible traces on everything from individual psychology to major social movements. Drawing on extensive field research, and with a special focus on Italy and the Netherlands, this interdisciplinary volume explores the interrelationship of migration and memory at scales both large and small, ranging across topics that include oral and visual forms of memory, archives, and artistic innovations. By engaging with the complex tensions between roots and routes, minds and bodies, The Mobility of Memory offers an incisive and empirically grounded perspective on a social phenomenon that continues to reshape both Europe and the world"
Includes bibliographical references and index
Keywords: Kollektives Gedächtnis; Soziale Bewegung; Randgruppe; Migration; Niederlande; Italien; Collective memory / Social aspects / Europe; Human geography / Europe; Europe / Emigration and immigration; Aufsatzsammlung